Activation of Periodate by Freezing for the Degradation of Aqueous Organic Pollutants - Choi, Yejin; Yoon, Ho-Il; Lee, Changha; Vetráková, L'ubica; Heger, Dominik; Kim, Kitae; Kim, Jungwon (Environmental science & technology, 2018)
A new strategy (i.e., freezing) for the activation of IO4- for the degradation of aqueous organic pollutants was developed and investigated. Although the degradation of furfuryl alcohol (FFA) by IO4- was negligible in water at 25 °C, it proceeded rapidly during freezing at -20 °C. The rapid degradation of FFA during freezing should be ascribed to the freeze concentration effect that provides a favorable site (i.e., liquid brine) for the proton-coupled degradation process by concentrating IO4-, FFA, and protons. The maximum absorption wavelength of cresol red (CR) was changed from 434 nm (monoprotonated CR) to 518 nm (diprotonated CR) after freezing, which confirms that the pH of the aqueous IO4- solution decreases by freezing. The degradation experiments with varying experimental parameters demonstrate that the degradation rate increases with increasing IO4- concentration and decreasing pH and freezing temperature. The application of the IO4-/freezing system is not restricted to FFA. The degradation of four other organic pollutants (i.e., tryptophan, phenol, 4-chlorophenol, and bisphenol A) by IO4-, which was negligible in water, proceeded during freezing. In addition, freezing significantly enhanced the IO4--mediated degradation of cimetidine. The outdoor experiments performed on a cold winter night show that the IO4-/freezing system for water treatment can be operated without external electrical energy.
Keywords: látky znečišťující životní prostředí; Periodic Acid; Environmental Pollutants; Water; zmrazování; kyselina jodistá; voda; Freezing